2021
DOI: 10.3389/fgene.2021.598296
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2, PDLIM5, BCL3, CD14, GBA Genes as Feasible Markers for Premature Coronary Heart Disease Risk

Abstract: Background: Beyond non-genetic risk factors, familial hypercholesterolemia (FH) plays a major role in the development of CHD. FH is a genetic disorder characterized by heritable and severely elevated levels of low-density lipoprotein (LDL) cholesterol, which can lead to premature cardiovascular disease, particularly familial coronary heart disease (FH-CHD).Method: To explore genes indicating a risk of familial (premature) coronary heart disease (FH-CHD) development in FH, 30 Thai male volunteers were enrolled:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Expression of BCL3 has been linked to CVD and cancer. 44-46 These examples provide proof of principle that integrating cis -mQTLs with CpGs and traits can reveal biological pathways by linking DNA methylation to a variety of diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Expression of BCL3 has been linked to CVD and cancer. 44-46 These examples provide proof of principle that integrating cis -mQTLs with CpGs and traits can reveal biological pathways by linking DNA methylation to a variety of diseases.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [134], ASB1 [135], OSM (oncostatin M) [136], ZNF791 [137], GBA (glucosylceramidase beta) [138], SOCS3 [139], SLC39A7 [140], AKIP1 [141], AMIGO2 [142], GLUL (glutamate-ammonia ligase) [143], SEMA4D [144], KDM2A [145], TP53 [146], JARID2 [147], CTBP1 [148], ATP6 [149], RPL7 [150], HSP90AA1 [151], BRD4 [152], PSMB4 [153], COX2 [154], JUND (JunD proto-oncogene, AP-1 transcription factor subunit) [155], RPS5 [156], RACK1 […”
Section: Discussionmentioning
confidence: 99%
“…TherapeuTic advances in cardiovascular disease (CHST15), 131 N-alpha-acetyltransferase 10, NatA catalytic subunit (NAA10), 132 transcription factor 3 (TCF3), 133 calponin 1 (CNN1), 134 TATA-box binding protein associated factor, RNA polymerase I subunit A (TAF1A), 135 acyl-CoA dehydrogenase family member 9 (ACAD9), 136 kelch-like family member 24 (KLHL24), 137 myomesin 2 (MYOM2), 138 tripartite motif containing 63 (TRIM63), 139 catenin alpha 3 (CTNNA3), 140 NLR family CARD domain containing 5 (NLRC5), 141 Kruppel-like factor 9 (KLF9), 142 myosin light chain kinase 3 (MYLK3), 143 RNA-binding motif protein 20 (RBM20), 144 glutathione S-transferase kappa 1 (GSTK1), 145 ubiquinol-cytochrome c reductase, Rieske iron-sulfur polypeptide 1 (UQCRFS1), 146 NADH: ubiquinoneoxidoreductase core subunit S2 (NDUFS2), 147 and cytochrome c oxidase subunit 6B1 (COX6B1) 148 have been reported to be positively correlated with cardiomyopathy. Genes include reticulon 4 (RTN4), 149 neutrophil cytosolic factor 2 (NCF2), 150 Rho GTPase activating protein 9 (ARHGAP9), 151 lipase G, endothelial type (LIPG), 152 BCL3 transcription coactivator (BCL3), 153 heparansulfate proteoglycan 2 (HSPG2), 154 apolipoprotein B receptor (APOBR), 155 integrin subunit alpha 2 (ITGA2), 156 peptidylprolylisomerase A (PPIA), 157 interleukin 1 receptor-associated kinase 1 (IRAK1), 158 vitamin K epoxide reductase complex subunit 1 (VKORC1), 159 renalase, FAD-dependent amine oxidase (RNLS), 160 major histocompatibility complex, class I, F (HLA-F), 161 F-box and leucine-rich repeat protein 17 (FBXL17), 149 collagen type XI alpha 2 chain (COL11A2), 162 and NADH: ubiquinoneoxidoreductase subunit C2 (NDUFC2) 163 are associated with prognosis of coronary heart disease. Genes include C-C motif chemokine receptor 1 (CCR1), 164 mesencephalic astrocyte-derived neurotrophic factor (MANF), 165 HSP90AA1, 166 ARRB2, 167 solute carrier family 39 member 13 (SLC39A13), 168 prolyl 4-hydroxylase subunit alpha 2 (P4HA2), 169 HECT domain E3 ubiquitin protein ligase 3 (HECTD3), 170 canopy FGF signaling regulator 2 (CNPY2), 171 enoyl-CoA hydratase domain containing 2 (ECHDC2), 172 NADH: ubiquinoneoxidoreductase subunit S4 (NDUFS4), 173 and inner membrane mitochondrial protein (IMMT)…”
Section: Carbohydrate Sulfotransferase 15mentioning
confidence: 99%